40 questions about Bible translation - Strauss, Mark L., 1959- (Grand Rapids, MI : Kregel Academic, 2023)
"The importance of Bible translation in historic and contemporary Christianity cannot be overstated, with millions around the globe reading and studying the Bible in their own language. Mark Strauss answers a wide range of questions about this essential reality of the Christian faith. 40 Questions About Bible Translation addresses questions related to the process and history of Bible translation; Bible versions and international translation efforts; and the multifaceted challenges in translating the Bible."--Back cover.
Part 1: The Necessity, Goals, and Methods of Bible Translation -- Why do we need Bible translation? -- What should be the goals of Bible translation? -- What are the main philosophies or methods of translation? -- What are the strengths and weaknesses of formal equivalence? -- What are the strengths and weaknesses of functional equivalence? -- Are there approaches that go beyond formal and functional equivalence? -- Part 2: Preparing to Translate -- Which books should be included in a Bible version? -- Which manuscripts should a Bible version follow? -- What other decisions must translators make? -- Part 3: Challenges for Translators -- A. Lexical Issues -- What are the Challenges of Translating Words? -- What are the challenges of translating collocations? -- B. Figurative Language -- What are the challenges of translating idioms? -- What are the challenges of translating poetry and metaphorical language? -- What are the challenges of translating other figures of speech? -- C. Cultural differences -- What are the challenges of translating implicit material? -- What are the challenges of translating euphemisms and other cultural features? -- What are the challenges of translating weights, measures, money, and time? -- D. Gender issues -- What are the issues related to gender language in Bible translation? -- What are the main translation issues in the gender-language debate? -- What are some controversial issues related to gender translation? -- E. Issues of Style, Structure, and Format -- How do translators determine chapters, verses, paragraphs and sections? -- What challenges arise in translating language related to God? -- Part 4: The History of (English) Bible Translation -- What were the earliest translations of the Bible? -- What were the earliest English translations of the Bible? -- What is the King James Version, and how did it come to be? -- Is the King James Version the most accurate English version today? -- What's wrong with the NT manuscripts behind the King James Version? -- When was the King James Version revised and why? -- What have been the main Roman Catholic Versions of the Bible? -- What were the earliest natural-language English versions? -- Part 5: Contemporary English Versions -- What are the most popular formal equivalent versions today? -- What are the most popular functional equivalent versions today? -- What are the most important mediating versions today (apart from the NIV)? -- What is the most popular English-language Bible today? -- Which versions blur the line between translation and commentary? -- Which versions most radically recontextualize the Bible? -- Part 6: International Bible Translation -- What are the main Bible versions in the world's major languages? -- How many languages still need a Bible, and who is doing this work? -- What are some of the challenges faced by international Bible translations? -- Wat is the controversy in translating "Son of God" in Muslim contexts?
Includes bibliographical references and index.
Keywords: Bible -- Translating; Bible -- Versions; Bible -- Versions; Bible -- Traduction; Bible